Demographics, Psychological Distress, and Pain From Pressure Injury. Issue 5 (September 2019) - Kim, Junglyun; Lyon, Debra; Weaver, Michael T.; Keenan, Gail; Stechmiller, Joyce
Abstract : Background: There is a knowledge gap regarding factors that influence the intensity of pain associated with pressure injuries. Objectives: We examined the influence of age, gender, race, and comorbidity on the relationships between pressure injuries, psychological distress, and pain intensity in hospitalized adults. Methods: This study was a cross-sectional, retrospective secondary analysis using data from a regional acute hospital's electronic health records from 2013 to 2016. A sample of 454 cases met the inclusion criteria and were analyzed using path analysis. Results: The hypothesized model (Model A) and two alternative models (Models B and C) were tested and demonstrated adequate model fit. All tested models demonstrated statistically significant independent direct effects of age on the severity of pressure injury ( p < .001) and pain intensity ( p = .001), as well as independent direct effects of gender ( p ⩽ .005), race ( p < .001), and comorbidity ( p = .001) on psychological distress. Discussion: Pain management for individuals with pressure injuries should include not only the treatment of wounds but also the individual characteristics of the patient such as demographics, comorbidity, and psychological status that may affect pain. Given the limitations of secondary analyses, further studies are suggested to validate these findings.